Wear mechanism of heterogeneous gas-thermal coatings on titanium alloy VT-22 - Киндрачук, М.В.; Кульгавый, Э.А.; Шевченко, А.Л. (Problems of Tribology, 2014)
The intensity of wear in tribological systems determines the properties of the structures of dissipative type which are formed in contact during running-in. In this paper we investigate the mechanism and regularities of the functioning of the tribological structures depending on the methods of gas-thermal coatings deposition and their influence on triboteсhnical characteristics.